Analisis Semiotik Pesan Dakwah dalam Film Pendek “Doa Suto” Pada Channel YouTube NU ONLINE - Muhammad Faqih; Ida Afidah; Hendi Suhendi (UNISBA Press, 2023)
Abstract. This research aims to find out what da'wah messages are contained in each scene of the Short Film